A NEW FUNGICIDE RIZOLEX AGAINST COLLAR ROT OF BETELVINE CAUSED BY SCLEROTIUM ROLFSll - R. K. S. TIWARI, A. L. DESHPANDE* AND (Indian Phytopathology, 2002)
RizolexÂ·S-3349 (tolclofos-methyl) in the form of dust (10 per cent) and wettable powder, 50 per cent (0.1 and 0.2 per cent) was tested alongwith foltaf 80 WP (0.2 per cent), bordeaux mixture (0.2 per cent) and "Palash" water soaked root extract (1 per cent) with a modified method in-uitro (on sorghum grains in artificially sick soil beds of betelvine garden "Bareja") and in-uiuo. Rizolex in both the form was highly significant in checking the growth of S. rolfsii and provided complete protection to betelvine crop against collar rot infection. Foltaf, bordeaux mixture, and "Palash" water soaked root extract were found almost ineffective. Dust form of rizolex was superior to wettable powder form considering the a.i. quantity per hectare. Modified method used in-uitro was found economical.